Benthic Macroinvertebrates as Bioindicators of Water Quality of Krueng Aceh Watershed Based on the BMWP-ASPT Method - Octavina, Chitra; Muchlisin, Zainal Abidin; Satriyo, Purwana; Hurzaid, Amirah (HAYATI Journal of Biosciences, 2026)
The Krueng Aceh watershed, vital to Banda Aceh and Aceh Besar, is increasingly threatened by ecological disruption from land-use changes that cause erosion, turbidity, and increased runoff. This study aimed to analyze the quality conditions of the Krueng Aceh River using benthic macroinvertebrates as bioindicators of BMWP-ASPT. The analysis was conducted from March to August 2024 and used a purposive sampling method. Observation stations were distributed at 10 points along the river, representing the upstream, middle, and downstream sections of the river. The upstream and middle sections of the river used surber nets, while the downstream section used PVC pipes to collect benthic macroinvertebrates. The assessment was based on community structure, the Biological Monitoring Working Party-Average Score Per Taxon (BMWP-ASPT) method, and physicochemical parameters of water and substrate. We recorded 29 macroinvertebrate families: 15 are in the original BMWP, and 14 additional families were incorporated to adapt the index. River health showed a clear longitudinal gradient, with upstream good, midstream moderate, and downstream poor, consistent with physicochemical patterns and downstream pressures. It is concluded that BMWP-ASPT is effectively adapted for diagnosing the condition of the Krueng Aceh watershed.